2016
DOI: 10.1007/s00430-016-0463-0
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of CF patients’ upper airways with S. aureus contributes more decisively to upper airway inflammation than P. aeruginosa

Abstract: In cystic fibrosis (CF) patients' airways, inflammatory processes decisively contribute to remodeling and pulmonary destruction. The aims of this study were to compare upper airway (UAW) inflammation in the context of Staphylococcus aureus and Pseudomonas aeruginosa colonization in a longitudinal setting, and to examine further factors influencing UAW inflammation. Therefore, we analyzed soluble inflammatory mediators in noninvasively obtained nasal lavage (NL) of CF patients together with microbiology, medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
2
7
0
Order By: Relevance
“…Concurrent co‐colonization with SA in either UAW or LAW did not influence NL cytokine dynamics upon de novo acquisition of PsA (Figure C). Of note, in a recent study we identified SA to contribute more decisively to UAW inflammation than PsA . Indeed, cytokine concentrations in NL were higher when SA was present, what mainly applied to the PsA‐free patients.…”
Section: Discussionmentioning
confidence: 75%
“…Concurrent co‐colonization with SA in either UAW or LAW did not influence NL cytokine dynamics upon de novo acquisition of PsA (Figure C). Of note, in a recent study we identified SA to contribute more decisively to UAW inflammation than PsA . Indeed, cytokine concentrations in NL were higher when SA was present, what mainly applied to the PsA‐free patients.…”
Section: Discussionmentioning
confidence: 75%
“…This suggests that SaeRS may play different roles in different stages of host cell-pathogen interactions. Several key steps of infection include bacterial colonization, proliferation, evasion of innate defenses, and cytotoxicity (Ji et al, 1999; Okumura and Nizet, 2014; Janhsen et al, 2016; McGuinness et al, 2016). It was clearly demonstrated that SaeRS is critical for S. aureus to adhere to and invade human epithelial and endothelial cells through regulation of adhesins and invasins (Giraudo et al, 1999; Liang et al, 2006; Sun et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Disease states that drive UA chronic inflammation, such as cystic fibrosis (CF), obstructive sleep apnea, CRS, and asthma, also impact the UA inflammatory profile and microbiota [ 65 ]. CF patients with higher colonization of S. aureus within their UAs had distinct levels of inflammatory biomarkers in nasal lavage samples [ 65 ]. Notable levels of IL-6, IL-8, IL-1β, MMP-9, and neutrophil elastase were detected [ 65 ].…”
Section: Ua Inflammationmentioning
confidence: 99%
“…CF patients with higher colonization of S. aureus within their UAs had distinct levels of inflammatory biomarkers in nasal lavage samples [ 65 ]. Notable levels of IL-6, IL-8, IL-1β, MMP-9, and neutrophil elastase were detected [ 65 ]. This suggests that increased colonization of S. aureus in diseased UAs could further contribute to the inflammatory response [ 65 ].…”
Section: Ua Inflammationmentioning
confidence: 99%
See 1 more Smart Citation